In Search of Originality in Central and Eastern European Legal Culture Culture(s). 4th Annual CEENELS Conference: Legal Innovativeness in Central and Eastern Europe, Moscow, 14–15 June 2019 - Szymaniec, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The paper describes the debates which took place during the 4th Annual CEENELS Conference (Moscow, 14–15 June 2019). The aim of the conference was to analyse the issue of legal innovativeness in Central and Eastern Europe, the topic which was chosen as a continuation of previous CEENELS conferences. The organizers wanted to challenge the widespread belief that the legal culture of Central and Eastern Europe lacks original and innovative concepts and ideas. Even if the conference did not bring a definitive answer about the character of Central and Eastern European countries’ legal culture, it showed that the region is not only a territory of legal transplants and reception of legal ideas, concepts and institutions, created in Western Europe or the US.